Infection-Induced Changes Within the Endocytic Recycling Compartment Suggest a Roadmap of Human Cytomegalovirus Egress - Close, William L.; Glassbrook, James E.; Gurczynski, Stephen J.; Pellett, Philip E. (Frontiers in Microbiology, 2018)
Human cytomegalovirus (HCMV) is an important pathogen in developing fetuses, neonates, and individuals with compromised immune systems. Gaps in our understanding of the mechanisms required for virion assembly stand in the way of development of antivirals targeting late stages of viral replication. During infection, HCMV causes a dramatic reorganization of the host endosecretory system, leading to the formation of the cytoplasmic virion assembly complex (cVAC), the site of virion assembly. As part of cVAC biogenesis, the composition and behavior of endosecretory organelles change. To gain more comprehensive understanding of the impact HCMV infection has on components of the cellular endocytic recycling compartment (ERC), we used previously published transcriptional and proteomic datasets to predict changes in the directionality of ERC trafficking. We identified infection-associated changes in gene expression that suggest shifts in the balance between endocytic and exocytic recycling pathways, leading to formation of a secretory trap within cVAC. Conversely, there was a corresponding shift favoring outbound secretory vesicle trafficking, indicating a potential role in virion egress. These observations are consistent with previous studies describing sequestration of signaling molecules, such as IL-6, and the synaptic vesicle-like properties of mature HCMV virions. Our analysis enabled development of a refined model incorporating old and new information related to the behavior of the ERC during HCMV replication. While limited by the paucity of integrated systems-level data, the model provides an informed basis for development of experimentally testable hypotheses related to mechanisms involved in HCMV virion maturation and egress. Information from such experiments will provide a robust roadmap for rational development of novel antivirals for HCMV and related viruses.